From combined therapy to fixed-dose combinations - I. P. Kolos; S. A. Boytsov (Кардиоваскулярная терапия и профилактика, 2008)
Due to low effectiveness of arterial hypertension (AH) monotherapy, recent debates have concentrated on evidence-based effectiveness and safety of combined AH therapy. To improve treatment compliance, reduce treatment costs, and increase therapy effectiveness, fixed-dose combined antihypertensive therapy is used more and more actively. One of such fixed-dose combinations, with proved effectiveness and safety, is Tarka medication, including trandolapril and verapamil. The article reviews the literature data demonstrating fixed-dose trandolapril+verapamil combination effects on blood pressure level and target organ damage in AH, renal failure, diabetes mellitus, and coronary heart disease.